THE ROLE OF LEARNING MOTIVATION AS A MEDIATION OF INFLUENCE OF SELF-EFFICACY (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
This study aims at determining the direct and indirect effect of self-efficacy and learning environment on economics learning achievement of eleventh graders at Senior High School 27 Bandung through learning motivation. The sample of this research are120 eleventh grade students atSenior High School 27 Bandung. The data were collectedusing questions and questionnaires, and they were analyzedbyusing descriptive analysis and path analysis. Based on the results of the study, it was found that there was a direct influence of self-efficacy on learning achievement. There was a direct influence of the learning environment on learning achievement, and there was an influence of learning motivation on learning achievement. The results also showed that there was an indirect effect of self-efficacy and learning environment on learning achievement through learning motivation. Based on the t-test, the effect of self-efficacy on learning achievement is 3.919, the influence of the learning environment is 3.315, the influence of learning motivation is 6.410. The indirect effect of self-efficacy on learning achievement through learning motivation is 0.140, and the indirect effect of the learning environment on learning achievement through learning motivation is 0.290.